A run at love [large type] - Shiloh, Toni (Shiloh, Toni. Love in the spotlight, 2024)
"As a Black woman in a field with little diversity, Piper McKinney is determined to make her mark on the horse-racing world. Raised on a Thoroughbred farm in Kentucky, Piper's dream is for her horse to win the prestigious Kentucky Derby. With the help of her best friend and trainer, Tucker Hale, she gains national attention but must grapple with the complications that arise when a journalist delves into her past as a transracial adoptee. In an effort to win Piper's heart, Tucker formulates a plan to train Piper's horse to victory, hoping to prove himself to her, her parents, and his own self-doubts. Then a shocking scandal hits the media, implicating both Piper and her parents, and she and Tucker will have to survive the onslaught to find their way to the winner's circle--and each other." --